2014
DOI: 10.1007/s10140-014-1200-x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of additional CT examinations driven by completion of a standard trauma imaging protocol in patients transferred for minor trauma

Abstract: Many clinicians order focused computed tomography (CT) examinations for trauma patients based on history and physical examinations. Trauma patients transferred to our level I trauma center undergo an extensive, nonfocused standard trauma CT protocol. We hypothesize that the use of the standard trauma CT protocol does not contribute significant clinical information for patient care when compared with CT examinations based on history and physical examination. We aim to quantify the utility of the additional CT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although CT scanning for ED trauma evaluation rose more than fourfold between 2000 and 2007, outpacing overall CT growth in the ED, there does not appear to have been an accompanying increase in the diagnostic prevalence of life‐threatening conditions during this time . Nevertheless, CT (including whole‐body CT) is often routinely recommended in trauma, with wide practice variation seen geographically and by specialty . CT scanning for trauma occurs disproportionately in younger patients, who may be more susceptible to radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CT scanning for ED trauma evaluation rose more than fourfold between 2000 and 2007, outpacing overall CT growth in the ED, there does not appear to have been an accompanying increase in the diagnostic prevalence of life‐threatening conditions during this time . Nevertheless, CT (including whole‐body CT) is often routinely recommended in trauma, with wide practice variation seen geographically and by specialty . CT scanning for trauma occurs disproportionately in younger patients, who may be more susceptible to radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in these positive studies were included if they had significantly altered mental status and/or high injury severity scores, which represents a relatively small subset of all trauma patients. Further studies comparing the benefits of “panscan” versus targeted imaging of body regions are needed that take into account morbidity, mortality, radiation exposure, expense, cost, and potential for incidental or clinically insignificant findings …”
Section: Resultsmentioning
confidence: 99%
“…According to BABAUD et al, the proportion of abnormal whole body scanner is significantly higher in the group of patients who received a targeted scan than those who received a justified whole body scanner only by the presence of Vittel criterion [3]. On the other hand, HELLER et al in 2014 got, out of 481 whole body scanner oriented by anamnesis and clinic, only 1.5% of lesions with only minor traumas lesion [13]. Our figures are lower than those obtained by OBERLIN et al, who found in their multifaceted study 55.8% of computed tomography lesions in a population of 429 patients based on TRENAU classification who correct the parameters of Vittel criteria [10].…”
Section: Discussionmentioning
confidence: 99%
“…This has led some centers to use CT scanning of the torso liberally [5][6][7][8][9]. Whereas others advocate for use in selected patients [10,11]. Advocates of selective CT for trauma argue that the benefits do not outweigh the complications, which include IV contrast issues, radiation exposure, and cost [12][13][14].…”
Section: Introductionmentioning
confidence: 99%